Incidence of Escherichia coli producing Extended-spectrum beta-lactamase in wastewater of dairy farms in East Java, Indonesia - FIDI NUR AINI EKA PUJI DAMEANTI; SHEILA MARTY YANESTRIA; AGUS WIDODO; MUSTOFA HELMI EFFENDI; HANI PLUMERIASTUTI; WIWIEK TYASNINGSIH; RAHAYU SUTRISNO; M. ALI AKRAMSYAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Dameanti FNAP, Yanestria SM, Widodo A, Effendi MH, Plumeriastuti H, Tyasningsih W, Sutrisno R, Akramsyah MA. 2023. Incidence of Escherichia coli producing Extended-spectrum beta-lactamase (ESBL) in wastewater of dairy farms in East Java, Indonesia. Biodiversitas 24: 1143-1150. Poor wastewater treatment on dairy farms can potentially become environmental contaminants (hazardous chemicals, organic matter, and pathogenic bacteria). Bacteria from dairy cattle that have been resistant can be found in wastewater. It can migrate around the farm and cause resistance to environmental microbiota. Over the years, cases of antimicrobial resistance (AMR) in Escherichia coli bacteria are increasing due to the uncontrolled use of antibiotics in dairy farms. The present study aimed to identify the potential occurrence of dairy farm wastewater as a reservoir for Extended-Spectrum Beta-Lactamase (ESBL)-producing E. coli in East Java. The number of research samples used was 342 and came from 6 cities/regencies with the highest dairy cattle population in East Java (Pasuruan District, Malang District, Tulungagung District, Blitar District, Batu City, and Kediri District). The results showed that 69.30% (237/342) of dairy farm wastewater samples were positive for E. coli. The incidence of Escherichia coli AMR was 99.17% (235/237). The resistance conditions to each class of antibiotics were 76.4% ampicillin, 66.2% cefotaxime, 37.6% tetracycline, 15.6% ciprofloxacin, 96.2% streptomycin, 16.5% sulfamethoxazole-trimethoprim, and 84.0% chloramphenicol. The incidence of E. coli MDR was 84.25% (198/235), with the highest incidence (44.44%; 88/198) found in the four groups of antibiotics. The incidence of ESBL-producing E. coli from samples of dairy farm wastewater in East Java through DDST confirmation was 22.80% (78/342), with the highest incidence (20.51%; 16/78) in Pasuruan District and Batu City. In conclusion, dairy farm wastewater could be a reservoir for ESBL-producing E. coli which has the potential to impact human health in East Java Province.